Upaya Penyembuhan Alopesia Androgenetik Melalui Obat-Obatan Baru Untuk Meningkatkan Kualitas Hidup Laki-Laki - Maryam Hasymia Ishmatullah (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2020)
Baldness in men can affect social interactions, thereby reducing quality of life. The type of baldness that most often affects men is Androgenetic Alopecia (AGA) which is caused by hormonal and gene factors. Efforts to find new drugs for AGA therapy are continuing. Various drugs that are currently being developed are Clascoterone with hormonal blocking mechanism; FOL-005 with affecting network repair mechanism; Cysclospoerine with inhibiting hair growth mechanism